Evidence of microplastics (MP) in gut content of major consumed marine fish species in the State of Kuwait (of the Arabian/Persian Gulf). (May 2020) - Al-Salem, S.M.; Uddin, Saif; Lyons, Brett
Abstract: Microplastics (MP), the debris that collectively refers to plastic fragments and particles of <5 mm in size within marine environments, has been the subject of interest within the past decade. Evidence of its occurrence and abundance, has been recorded in this communication after examining gastrointestinal specimens of eight commercially available fish species common to the Arabian (Persian) Gulf acquired locally from the State of Kuwait. The species studied belonged to different trophic levels, and the specimens were subjected to Micro Raman and Micro Fourier Infrared Spectroscopy (FTIR) in Attenuated Reflective Mode (ATR) to determine the presence and type of polymer of the MP. The detected MP set a president for the first time in the examined fish species within the State of Kuwait, which are of immense commercial importance. Various particles were detected, and three MP particles (fragments) were detected within the guts of Acanthopagrus latus, Eleutheronemaa tetradactylum and Lutjanus quinquelineatus . Based on the nature and behaviour of these particular fish types which prefer to stay in muddy waters and sheltered lagoons, it is suspected that common primary sources of MP (i.e. waste fragmentation) have led to passive/active intake (e.g. detritus ingestion) of these particles (fragments) by these species of fish in Kuwait. Graphical abstract: Unlabelled Image Highlights: Evidence of MP presence in fish guts is recorded in Kuwait Eight different species were studied and acquired locally. Evidence in three types of fish belonging to different trophic levels was recorded. Polyethylene was determined to be the type of polymer constituting the MP.